Peran SD Negeri 15 Banyuasin III dalam Meningkatkan Pendidikan Karakter Siswa - Sariwani, Desi (Yayasan Sembilan Pemuda Indonesia, 2025)
Character education is an essential aspect of student development in elementary schools. This study aims to analyze the role of SDN 15 Banyuasin III in enhancing students' character education. The research employs a qualitative method with data collection techniques including interviews, observations, and questionnaires. The findings indicate that SDN 15 Banyuasin III has implemented various effective character education programs, such as extracurricular activities and moral value training. Furthermore, the active participation of teachers and parents significantly contributes to the success of these programs. However, challenges in implementation, such as resource limitations and a lack of understanding of character education, were identified. This study recommends enhancing collaboration between the school and the community to optimize character education at SDN 15 Banyuasin III.